2004
DOI: 10.1093/humrep/deh308
|View full text |Cite
|
Sign up to set email alerts
|

Best site for embryo transfer: the upper or lower half of endometrial cavity?

Abstract: The implantation or pregnancy rates were similar whether the embryos were deposited in the upper or lower half of the endometrial cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Among these factors are ultrasound guidance, transfer catheter type, catheter-loading technique, uterine cavity fluid, blood or mucus effects, retained embryos, mock transfer, myometrial contractions, and facility of the procedure. In addition to these variables, the site of embryo placement in the uterine cavity has recently been postulated to influence embryo implantation rates (9)(10)(11)(12)(13). In their study, Frankfurter et al (9) analyzed their videotapes of embryo transfers in pregnant and nonpregnant cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these factors are ultrasound guidance, transfer catheter type, catheter-loading technique, uterine cavity fluid, blood or mucus effects, retained embryos, mock transfer, myometrial contractions, and facility of the procedure. In addition to these variables, the site of embryo placement in the uterine cavity has recently been postulated to influence embryo implantation rates (9)(10)(11)(12)(13). In their study, Frankfurter et al (9) analyzed their videotapes of embryo transfers in pregnant and nonpregnant cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the discussion regarding the best site within the endometrial cavity for embryo transfer preserves its actuality, a study by Franco et al (13) claimed that this question was of no importance as the site of embryo transfer did not influence implantation rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of air bubbles next to embryos in the uterus does not cause embryo expulsion, studied during mock transfers using methylene blue marker [8]. A wide window of implantation with similar pregnancy rates was observed when the uterus was divided into upper and lower half cavities [9]. Additional support of this practice came from studies that demonstrated that 80% of embryo implantations occurred in the original area of transfer [10].…”
Section: Discussionmentioning
confidence: 98%